COG6‐CDG: Novel variants and novel malformation. Issue 5 (23rd January 2022) - Cirnigliaro, Lara; Bianchi, Paolo; Sturiale, Luisa; Garozzo, Domenico; Mangili, Giovanna; Keldermans, Liesbeth; Rizzo, Renata; Matthijs, Gert; Fiumara, Agata; Jaeken, Jaak; Barone, Rita
Abstract: Background: Deficiency of Conserved Oligomeric Golgi (COG) subunits (COG1–8) is characterized by both N‐ and O‐protein glycosylation defects associated with destabilization and mislocalization of Golgi glycosylation machinery components (COG‐CDG). Patients with COG defects present with neurological and multisystem involvement and possible malformation occurrence. Eighteen patients with COG6‐CDG ( COG6 mutations) were reported to date. We describe a patient with COG6‐CDG with novel variants and a novel clinical feature namely a congenital recto‐vaginal fistula. Methods: In‐depth serum N‐ and O‐glycosylation structural analyses were conducted by MALDI‐TOF mass spectrometry. COG6 variants were identified by a gene panel and confirmed by Sanger sequencing. Results: This female newborn presented with facial dysmorphism, distal arthrogryposis and recurrent stool discharges per vaginam. A double‐contrast barium‐enema X‐ray study revealed a dehiscence (approximately 5 mm) at the anterior wall of the rectal ampoule communicating with the vagina consistent with a recto‐vaginal fistula. She had developmental delay, corpus callosum dysgenesis, liver and gastrointestinal involvement, hyperthermia episodes and early demise. Serum N‐ and O‐glycosylation analyses pointed to a profound Golgi disarrangement. We identified two novel variants in COG6: a deletion of 1 bp mutation c.823delA creating a shift in the reading frame and a premature stop codon and a 3 bp deletion (c.1141_1143delCTC) producing an in‐frame deletion of 1 amino acid. Conclusion: The congenital recto‐vaginal fistula is a rare type of anorectal malformation that, to our knowledge, has not been reported in patients with a COG6 defect nor in patients with other COG defects. This study broadens COG6‐CDG genetic landscape and spectrum of malformations.